Michel de Certeau and the historiography of everyday life: A self-reflective encounter through Iranian cultural studies - H. Aghajanzadeh (Taḥqīqāt-i Farhangī-i Īrān)
The acquaintance with Michel de Certeau in Iran was made possible through a specific framework derived by John Fiske from Certeau's book, "The Practices of Everyday Life," focusing particularly on the two concepts of strategy and tactics. Fiske's approach toward Certeau's perspectives, while overlooking his methodological framework, aims at universalizing the aforementioned concepts and aligning "ways of operating" with "ways of media consumption". Nevertheless, Certeau is known as a multifaceted and intellectually affluent scholar, renowned for his significant contributions at the crossroads of historiography, psychoanalysis, theology, linguistics, and anthropology. His methodological and epistemological insights into the field of historiography, especially the important discussion about "The Historiographical Operation" - which has been an attempt to frame historical studies within meta-historiography - can serve as a suitable foundation for further exploration. Given the shift toward historiographical projects focusing on everyday life in Iran, his work provides a valuable starting point. It is imperative to navigate beyond the confusion that has obstructed the study of everyday life in Iran toward a historiographical undertaking. This article delves into elucidating the foundational tenets of Certeau's "meta-historiography," distinguishing it from Hayden White's metahistorical perspectives. Subsequently, these methodological and meta-methodological considerations are highlighted in light of one of his renowned historical monographs "The Possession at Loudun”.  Furthermore, through a self-reflective engagement, I aim to explore the consequences of stepping aside from Certeau within Iranian cultural studies, examine the constraints of conjunctural analysis in the historiography of everyday life, and explore the potential of meta-historiography to alleviate current obstacles.